Un achegamento á tradución para a dobraxe en Galicia - Montero Domínguez, Xoán (Madrygal. Revista de Estudios Gallegos, 2005)
This research work focuses on translation for dubbing purposes in Galicia. Firstly, we discuss the skills that should be developed by linguistic mediators willing to work in this field of translation. Secondly, we comment on certain specific problems concerning translators and translation in Galicia. .